Ответы и объяснения

2014-03-03T17:39:23+04:00
А)H2CO3 + 2 NaOH = Na2CO3 + 2H2O
2H(+)+CO3(2-)+2Na(+)+2OH(-)=2Na(+)+CO3(2-)+2H2O
2H(+)+2OH(-)=2H2O |:2
H(+)+OH(-)=H2O

б)Ca(NO3)2+K2CO3=CaCO3+2KNO3
Ca(2+)+2NO3(-)+2K(+)+CO3(2-)=CaCO3+2K(+)+2NO3(-)
Ca(2+)+CO3(2-)=CACO3

в)
2FeCl3 + 3Ca(OH)2 =2 Fe(OH)3 + 3CaCl2
2Fe(3+)+6Cl(-)+3Ca(2+)+6OH(-)=2Fe(OH)3+3Ca(2+)+6Cl(-)
2Fe(3+)+6OH(-)=2Fe(OH)3 |:2
Fe(3+)+3OH(-)=Fe(OH)3

г)
2H3PO4+3Cа (OH)2=Ca3(PO4)2+6H2O

д)СuСl2+H2S=CuS+2HCl
Cu(2+)+2Cl(-)+2H(+)+S(2-)=CuS+2H(+)+2Cl(-)
Cu(2+)+S(2-)=CuS